2006
DOI: 10.1051/agro:2006002
|View full text |Cite
|
Sign up to set email alerts
|

High sorption of phenanthrene in agricultural soils

Abstract: We studied the sorption and desorption of 14 C-labelled phenanthrene, a polycyclic aromatic hydrocarbon, on soils, both in the laboratory using batch experiments and during 6 months of natural conditions using lysimeters. The laboratory results show that phenanthrene is strongly adsorbed, yielding empirical constants of sorption isotherms K f of 163 for the clay soil and of 77 for the sandy loam soil. This result is unexpected because phenanthrene has a relatively high water solubility of 1.1 mg/L. Phenanthren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 24 publications
(23 reference statements)
1
10
0
Order By: Relevance
“…Amellal et al (2006) confirmed that phenanthrene was strongly adsorbed in clay soil rather than sandy-loam soil (constant of sorption isotherm was two times higher in the clay soil). Moreover, this study outlined the importance of using plants in clay soils.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Amellal et al (2006) confirmed that phenanthrene was strongly adsorbed in clay soil rather than sandy-loam soil (constant of sorption isotherm was two times higher in the clay soil). Moreover, this study outlined the importance of using plants in clay soils.…”
Section: Discussionsupporting
confidence: 53%
“…Asterisk indicates significant difference between polluted and non-polluted soil treatments for each kind of soil (Chisquare, P < 0.05) Asterisk indicates significant difference between polluted and non-polluted soil treatments for each kind of soil (Chisquare, P < 0.05) process (Sheng and Gong 2006;Amellal et al 2006). Time was required to restore micro-organism populations from the initial dry soils.…”
Section: Discussionmentioning
confidence: 99%
“…There also exists a large literature on sorption studies conducted with natural minerals and other geosorbents, like sediments or soils, with varying organic matter content [88][89][90][91][92][93][94][95][96][97][98][99][100][101]. For example, the interaction between the (110) goethite surface and acetic acid, acetate, 2,4-dichlorophenoxyacetic acid, 2,4-dichlorophenoxyacetate and benzene have been studied by means of quantum mechanical calculations using the B3LYP approach [88], whereas the interaction of esters and acids with iron oxide surfaces has also been reported [47,89].…”
Section: Introductionmentioning
confidence: 99%
“…The negative correlation of K OC with OC and NCOC at Estrup suggests that the capacity of organic matter to sorb phenanthrene decreases at higher OC contents. This decreasing efficiency can be related to the SOM quality and the amount of OC that can be readily retained (Amellal et al 2006). The hydric regime, microbial activity and other factors can change the degradation rates, affecting the composition of the SOM (e.g., Styrishave et al 2012).…”
Section: Soil Propertiesmentioning
confidence: 99%